Lightweight rowers` perspectives of living with Relative Energy Deficiency in Sport (RED-S) - Gillbanks, L.; Mountjoy, M.; Filbay, S. R. (PLOS ONE, 2022)
Objective: To compete in lightweight rowing, strict limits are placed on the maximum body weight of each individual. As a result, lightweight rowers commonly restrict calorie intake despite high energy expenditure. This can result in Relative Energy Deficiency in Sport (RED-S). The aim of this study is to investigate the physical and psychosocial impact of RED-S, from the perspective of lightweight rowers. Design: Semi-structured individual qualitative interviews. Participants: Adults living in the United Kingdom who are current or former lightweight rowing participants and experienced =1 symptom of RED-S. Method: Audio-recorded semi-structured individual telephone interviews were performed. Data was analysed using an inductive thematic approach, coding was iterative and data-driven, facilitated by NVivo software. Results: Twelve current or former lightweight rowers (intermediate to international standard, 67% female, aged 19-32 years) participated. Participants restricted calories and increased energy expenditure to elicit weight-loss in order to meet weight requirements. This resulted in psychosocial implications (reduced social interaction, difficulty maintaining relationships, poor emotional regulation, low mood, poor concentration, disordered eating, guilt and anxiety around food, and a negative body image). Some psychosocial implications persisted after retirement from lightweight rowing. Participants described a range of physical implications, including disrupted sleep, decreased performance and recovery, bowel disruption, menstrual dysfunction, fatigue, musculoskeletal pain, injury and weakened immune systems. Conclusions: This study describes short and long-term physical and psychosocial impacts of RED-S from the perspective of lightweight rowers. Findings highlight the importance of effective RED-S prevention and management strategies for lightweight rowers. These findings may be used to educate health-care professionals, coaches and athletes on the personal impacts and serious health consequences of RED-S.